PENERAPAN PEMBERIAN JUS WORTEL UNTUK PENURUNAN NYERI DISMINOREA PADA SISWI KELAS 8 DI SMP YP SINGOSARI DELI TUA TAHUN 2024 - Hutabarat, Vitrilina -; Insani, Septa Dwi (INSTITUT KESEHATAN DELI HUSADA, 2024)
Dysmenorrhea is a condition where there is pain during menstruation which is felt by cramps in the lower abdomen and is sometimes accompanied by headaches and an unstable psychological state. This community service activity was carried out at Yp Singosari Deli Tua Middle School, Deli Serdang Regency for three full weeks, starting on October 15, 2023. This method is in the form of conveying individual knowledge and skills using learning or instruction aimed at converting or influencing human actions both in society and groups, or individuals can be more independent in achieving counseling targets. The results of field observations were used as a basis for strengthening the concept of counseling which was delivered in the form of training on the benefits of giving carrot juice to reduce dysmenorrhoea pain at Singosari Delitua Middle School. Singosari Delitua did not know that the benefits of carrot juice could reduce dysmenorrhea pain. By providing coaching and mentoring using the counseling method, results were obtained where teenage female students who took part in the counseling program showed enthusiasm and curiosity about the benefits of carrot juice in reducing dysmenorrhea pain. Then a process of exchanging information was carried out with teenage female students and sharing experiences in solving problems related to counseling challenges. giving carrot juice to reduce dysmenorrhea pain. Increased knowledge of teenage female students who took part in counseling on the benefits of carrot juice to reduce dysmenorrhea pain.